Community Food Security and Florida Cooperative Extension Service - Alison E. Lutz; Nick T. Place; Mickie E. Swisher (EDIS)
AEC-384, a 4-page fact sheet by A.E. Lutz, N.T. Place and M.E. Swisher, defines community food security and identifies its importance for extension agents in Florida. Includes references and a table corresponding community food security concepts and extension focus areas. Published by the UF Department of Agricultural Education and Communication, May 2007.